Use of Chamomile Flower Powder (Matricaria Recutita) and its Effect on the Physical and Chemical Indicators in the Blood of Broiler - Mariya M. Abdullah (American Journal of Botany and Bioengineering, 2026)
This study was conducted in the poultry farms of the Animal Production Unit/College of Medicinal and Industrial Plants/University of Kirkuk, from 15/5 to 18/6/2024 to determine the effect of adding chamomile flowers to the diets of Rose 308 broiler chickens on some physical and biochemical blood characteristics for a period of 35 days. Unsexed Rose 308 chicks were used, divided into 4 treatments and 4 replicates. Each treatment included 60 chicks (15 chicks per replicate) in a floor-rearing system using 90 x 200 cm cage. The chicks were randomly distributed among the following treatments: Treatment (T1) was the control with no feed additives; (T2) received 1 g/kg of chamomile flower extract; (T3) received 2 g/kg of chamomile flower extract; and (T4) received 3 g/kg of chamomile flower extract. The results showed significant differences (p<0.05) in protein, albumin, globulin, glucose, cholesterol, and LDL concentrations when ginger powder was added compared to the control treatment. The addition of different levels of chamomile flower powder contributed to an improvement in serum lipid profile, with a significant decrease in total cholesterol, triglycerides, low-density lipoprotein (LDL), and very-low-density lipoprotein (VLDL) concentrations, and a significant increase in high-density lipoprotein (HDL) concentration, compared to the control treatment. The results also showed that the addition of chamomile flower powder did not negatively affect some basic hematological parameters, such as hemoglobin concentration, indicating its safety and lack of adverse hematological effects. Furthermore, an improvement in red blood cell count was observed in the chamomile-supplemented treatments compared to the control treatment, reflecting a supportive effect on the overall health of the birds.